2013
DOI: 10.1016/j.ejvs.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentric Experience with Open Surgical Repair and Endovascular Exclusion of Popliteal Artery Aneurysms

Abstract: In this large multicentric retrospective registry, open and endovascular treatment of PAAs are used in different patients with regard to clinical and anatomical characteristics. Both treatments are feasible and safe, providing satisfactory early and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 18 publications
6
102
1
8
Order By: Relevance
“…[31][32][33][34] Cases repaired with great saphenous vein grafts by conventional surgery have patency of 78.80% to 87.50% in the first year, with limb salvage rates of 94.30%. 20,26 Our patient sample was comparable with previous studies, with stent patency of 80% during the first year and limb survival of 100% over the first 90 days after ES, while cases treated with OS had 95.23% patency in the first month and 75% after 1 year, and a 90-day limb survival rate of 95.23%, including emergency cases. It is important to remember that in the cases treated with the endovascular technique, intraoperative arteriography showed at least two patent infrapatellar vessels, which indicates good blood flow drainage and contributes to the patency of the stents.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…[31][32][33][34] Cases repaired with great saphenous vein grafts by conventional surgery have patency of 78.80% to 87.50% in the first year, with limb salvage rates of 94.30%. 20,26 Our patient sample was comparable with previous studies, with stent patency of 80% during the first year and limb survival of 100% over the first 90 days after ES, while cases treated with OS had 95.23% patency in the first month and 75% after 1 year, and a 90-day limb survival rate of 95.23%, including emergency cases. It is important to remember that in the cases treated with the endovascular technique, intraoperative arteriography showed at least two patent infrapatellar vessels, which indicates good blood flow drainage and contributes to the patency of the stents.…”
Section: Discussionsupporting
confidence: 72%
“…They accounted for 52.38% of the indications for repair using this technique, with an acceptable amputation rate (4.76% of all OS and 9% of urgent operations). A study by Pulli et al 26 reported that the majority of patients who underwent OS were symptomatic, compared with ES, although some studies report equal success rates for elective and emergency surgery. 27 The great majority report rates of complications and limb loss of 10% to 36% for patients who undergone emergency surgery, which are comparable to the rates for our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the indications for repair of PAAs are not well defined, a diameter greater than 2 cm to 3 cm, especially for aneurysms with a significant thrombus load or with chronic distal tibial artery embolic occlusion, is an acceptable indication for intervention [11, 12]. Patients with severe claudication, resting pain, and tissue loss are considered for elective repair, as are patients who have symptoms of local compression.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have directly compared outcomes after OPAR with EPAR and with different methodologies 49 and there is only one published, prospective, randomized trial that evaluated outcomes after OPAR and EPAR that included only 30 patients. 5 …”
Section: Introductionmentioning
confidence: 99%